A constituiç\~ao de um modelo de atenç\~ao à saúde universal: Uma promessa n\~ao cumprida pelo SUS? - Carlos Octávio Ocké-Reis (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– In 1988 Brazil was one of the first Latin American countries to frame access to health care as a constitutional right, but, in fact, it has not produced coverage of its citizens. Brazil's Unified Health System (Sistema Único de Saúde, or SUS in Portuguese) cannot quite be described as a public health system that provides universal access and comprehensive care. This article reveals that there seems to be a strong contradiction between the redistributive model set in the Brazilian Constitution and the inadequate level of public spending on health. On the one hand, the law claims that health care is a basic social right, allocated by need rather than by affordability. In 2003, on the other hand, Brazil spent just US 597 per capita on health or 7.6 percent of its GDP, while the average country according to OECD spent US 3,145 or 10.8 percent, and the average Latin American country spent US 622 or 6.7 percent of its GDP.
Keywords: H51; I18; P05; 330